Impact of Personality Traits on Green Budgeting: The Mediation Role of Environmental Concern and Locus of Control - Eka Ardhani Sisdyani; Ni Made Dwi Ratnadi; I Putu Sudana; I Gusti Ayu Manuati Dewi; A.A Vidyaswari Kedisan (Universitas Hayam Wuruk Perbanas, 2023)
This study examines the influence of environmental concern and locus of control on the relationship between personality traits and the intention to implement green budgeting. Data was gathered through questionnaires distributed to 269 managers of regional organizations in Bali Province. The analysis utilized the partial least squares method. The findings indicate a positive impact of personality traits on the intention to implement green budgeting. This relationship is fully mediated by environmental concern, openness to experience, extraversion, and neuroticism. Additionally, the personality trait of conscientiousness is partially mediated by environmental concern. Furthermore, locus of control partially mediates the influence of personality trait agreeableness on the intention to implement green budgeting. In light of these results, increasing environmental awareness, especially with regard to individual factors like agreeableness (interpersonal harmony) and locus of control from the budget holders, can enhance the intention to implement green budgeting. This can be achieved through education and self-development programs. The implications for budgeting policies are to provide recommendations for strategy and program planning that contribute to the enhancement of environmental quality.